Influence of Persistent Inflammation in Follow-Up Biopsies After Antibody-Mediated Rejection in Kidney Transplantation - Piñeiro, Gaston J.; Montagud-Marrahi, Enrique; Ríos, José; Ventura-Aguiar, Pedro; Cucchiari, David; Revuelta, Ignacio; Lozano, Miquel; Cid, Joan; Cofan, Frederic; Esforzado, Nuria; Palou, Eduard; Oppenheimer, Federico; et al. (Frontiers in Medicine, 2021)
Background: Despite recent advances in immunosuppression treatment, antibody-mediated rejection (ABMR) remains the leading cause of kidney graft loss. Information about prognostic markers and treatment’s efficacy is scarce. Methods: retrospective study with kidney recipients diagnosed of an active ABMR from January 1st, 2004 to December 31st, 2019 to explore the influence of persistent inflammation in follow-up biopsies on graft survival after ABMR treatment. Results: 116 patients were included. Active ABMR were treated with a combination of plasma exchange, intravenous immunoglobulin, rituximab and steroids. At six months of treatment, 63 (54.3%) patients presented a stabilization or improvement in kidney graft function. The effectiveness varied depending on the presentation timepoint between transplantation and rejection, being lower for those with a late ABMR (63% vs. 21% for early vs. late ABMR, respectively). Ninety patients (77%) underwent a control biopsy after ABMR treatment, from which 46 (51%) responded to treatment. Microvascular inflammation (MVI) persisted in 64 (71%) biopsies, whereas tubulitis persisted in 17 (19%) biopsies. Death-censored graft survival at one year was significantly lower in patients with persistent MVI (86% vs 95% without persistent MVI, P=0.002), or with persistent tubulitis (44% vs 66% without tubulitis, P=0.02). In the Cox Regression analysis, MVI (HR 4.50 [95%CI 1.35 - 14.96], P=0.01) and tubulitis persistence (HR 2.88 95%CI [1.24 – 6.69], P=0.01) in follow-up biopsies significantly increased the risk of graft failure. Conclusions: Persistent inflammation in follow-up biopsies after ABMR treatment was associated with an increased risk of graft loss, even without meeting Banff rejection criteria.